IN VITRO ANTIBACTERIAL EFFICACY OF LEAVES EXTRACT OF Centela asiatica AGAINST Vibrio harveyi AND Aeromonas hydrophila - Rukisah Rukisah; Diana Maulianawati; Jimmy Cahyadi (Indonesian Aquaculture Journal, 2019)
Disease infection is one of the limiting factors that affect productivity in aquaculture and has caused economic losses. Luminescent vibrios and motile aeromonas septicemia (MAS) are diseases caused by Vibrio harveyi and Aeromonas hydrophila bacteria, respectively. Certain plants have antimicrobial compounds and can potentially be used to treat the diseases, such as Centella asiatica. In the present study, the crude leaves extracts of C. asiatica were examined for its antibacterial potential using methanol solvents against V. harveyi and A. hydrophila bacteria. Different concentrations of 50 mg/mL and 100 mg/mL were checked for its antibacterial activity. The crude extract was also tested for phytochemistry content and LC50 using Brine Shrimp Lethal Assay. The crude extracts of C. asiatica showed a remarkable antibacterial activity with inhibition zone of 10.57 mm against A. hydrophila and 21.14 mm against V. harveyi. The phytochemistry test result showed that C. asiatica leaves contain alkaloid, phenol, and tannin compounds. The acute lethal concentration (LC50) of C. asiatica after 24 hours exposure to the extract mixture was 254 mg/L. The results confirmed the potential use of C. asiatica extracts as a source of antibacterial compounds.